Political and racial cronyism: Combating strategies on the production rate - Selvam, Heramban; Sivasamba Rao, Sharrven Rao; Janc, Suriyana; Rusais, Wirlintika; Ramesh, Subhashini; Muhamad Tamyez, Puteri Fadzline (Penerbit Universiti Malaysia Pahang, 2022)
Delightful Bakeries (KL) Sdn Bhd (DBKL) faces a storm of protests after netizens call for their goods to be boycotted. The boycott started by blaming Mr Alauddin of being a crooked crony of certain political leaders, charging that he had followed orders to stop DBKL's purchase of flour on racial grounds alone. This case study aims to discuss political and racial cronyism and the impact on the production rate at Delightful Bakeries (KL) Sdn Bhd. The main technique that has been used to gather the response and perspective of respondents is semi-structured interview. The analysis showed practice of cronyism does have high effect on production rate. On this basis, it is recommended to introduce an effective strategy to improves the production rate at Delightful Bakeries (KL) Sdn Bhd.